Interprofessional Intervention in Childhood Programmes at the Local Level: the Experience of the 24 Horas Program’s Case Management Boards - Muñoz Arce, Gianinna; Ponce Figueroa, Erica (Revista del CLAD Reforma y Democracia, 2021)
Interprofessional intervention -the joint work carried out by different professionals- is a highly sensitive aspect in the implementation of childhood programmes, since it constitutes a basic requirement for a comprehensive approach to the problems affecting children. This article discusses research results on the experience of interprofessional work developed in the Case Management Boards of the 24 Horas Program, promoted by the Government of Chile. Based on a qualitative case study, the complexities of the installation process of these interprofessional initiatives and the critical aspects of their operation are analysed. The findings suggest that the precariousness and rotation of the teams prevent the consolidation of interprofessional learning, and that there are no political or institutional guarantees in the territories for the integrated approach proposed by the program to become effective. The requirements for a change in the logic of childhood policies are discussed, where there is a shift from making professionals responsible for the success or failure of the designs, to a logic of team care that favours interprofessional collaboration, creativity and the capacity for agency of their members.
Keywords: Social Programs; Programs Implementation; Childhood; Children; Local Administration; Case Analysis; Chile